Animals in translation using the mysteries of autism to decode animal behavior - Grandin, Temple 1947-; Johnson, Catherine (Harcourt, 2006)
Animal scientist Temple Grandin argues that people with autism think the way animals think and draws from her experiences with autism to discuss how animals think, act, and feel.
Originally published: New York : Scribner, c2005.
Includes bibliographical references and index
Keywords: Animaux - Murs et comportement; Autisme; Animal behavior; Autism; Verhaltensforscher; Autismus; Tiere; Mensch